Reversal and non-reversal ferroelectric polarizations in a Y-type hexaferrite. Issue 2 (14th December 2018) - Wang, Yongqiang; Zhang, Shile; Zhu, W. K.; Ling, Langsheng; Zhang, Lei; Qu, Zhe; Pi, Li; Tong, Wei; Tian, Mingliang
Abstract : The Cr ion doped Y-type hexaferrite Ba0.5 Sr1.5 Zn2 Fe11.4 Cr0.6 O22 has been found to be a promising magnetoelectric material for the non-zero spontaneous electric polarization. A newly emerging transition at 183 K separates the low-field ferroelectric phase into two regions with reversal and non-reversal polarization respectively. Abstract : The Cr ion doped Y-type hexaferrite Ba0.5 Sr1.5 Zn2 Fe11.4 Cr0.6 O22 has been found to be a promising magnetoelectric material for the non-zero spontaneous electric polarization that can be reversed by a relatively low magnetic field. However, it remains an open question what the underlying mechanism of the magnetoelectric correlation is and how this correlation evolves with the varying temperature and magnetic field. Here we establish a detailed phase diagram via the combined measurements and analyses of magnetization, dielectric constant, and electric polarization. Various magnetic and ferroelectric phases are discovered for different scales of temperature and magnetic field, as well as the complicated and intriguing phase transitions. A newly emerging transition at 183 K separates the low-field ferroelectric phase into two regions with reversal and non-reversal polarizations, respectively, which is rarely observed among various magnetoelectric ferrites. Possible field-dependent magnetic structures are proposed to qualitatively explain this transition.